(untitled) (Research, Society and Development, 2020)
The tambaqui Colossoma macropomum is the most important native species of Brazilian fish farming, being produced especially in the Amazon region. In the state of Pará, commercial breeding occurs mainly in excavated pond and in net tanks or floating cages. The objective of this study was to analyze the production cost and profitability of creating tambaqui in the state of Pará. The operational cost structure and economic efficiency indicators were adopted to evaluate a fish farm with 12 excavated ponds of 1,200 m² each, in the municipality from Irituia/PA, and the creation of fish in 12 floating cages of 4 m3 of useful volume in Juruti/PA. In November 2015, the cost of implementing fish farming in excavated ponds was estimated at R 110,357.76 and the effective operating cost at R 79,661.92. Gross revenue was R 108,000.00, monthly operating profit of R 1,984.11, the internal rate of return of 25%, the net present value of R 72,914.16 and the period of capital return of 4,91 years. In December 2015, the cost of implementing fish farming in floating cages was estimated at R 24,576.72 and the effective operating cost at R 20,158.35. Gross revenue was R 27,000.00, monthly operating profit of R 380.13, the internal rate of return of 25%, the net present value of R 10,133.88 and the period of return on capital of 3,58 years. Fish farms proved to be profitable investments, with the capacity to maximize profit, if more appropriate productive strategies are adopted.